Using Trees to Monitor Airborne Cr Pollution: Effects of Compass Direction and Woody Species on Cr Uptake during Phytoremediation - Ayse Ozturk Pulatoglu; İsmail Koç; Halil Barış Özel; Hakan Şevik; Yafes Yıldız (BioResources)
Among the heavy metals (HMs) whose concentrations in natural environments have risen considerably in the last era, chromium (Cr) is one of the most toxic. Because of the risks it poses to human and environmental health, it is of great importance to screen the variation in Cr contamination in the atmosphere and decrease the pollution. This study aimed to determine the proper tree species that can be used to monitor and reduce Cr contamination. For this aim, studies were conducted on Tilia tomentosa, Robinia pseudoacacia, Cedrus atlantica, Pseudotsuga menziesii, and Fraxinus excelsior species growing in Düzce, which is among the 5 most contaminated European towns according to the World Air Pollution report. Samples taken from these trees were examined, and changes in Cr concentration depending on species, organs, compass direction, and age range in the last 60 years were evaluated. Results indicated higher Cr pollution in recent years, consistent with higher traffic density, but that there was no consistent effect of compass direction. It was also determined that the tree species most appropriate for screening the variation in Cr contamination in the airborne were Tilia tomentosa, and the most appropriate species for decreasing pollution were Robinia pseudoacacia and Cedrus atlantica.